E-mail alert via SMS / Mohd Fadhil Ab Rahman - Ab Rahman, Mohd Fadhil (2005)
This project is about email alert via SMS that were implementing at FTMSK. This project were implementing at FTMSK network. Email and short messaging technology is important services now, especially to a person who busy with their work. Significant of this project is to make email technology at faculty become effective and efficient among student and lecturer. The advantages of this project are to make student more alert with their mail. Student always alert with every mail that through in their mail box, by SMS. Beside that student know when to check their mail. They only go check their mail if get SMS, that save their time and energy. In this project, discussed about what Email and SMS can do, why used email alert and, How to implement Email must alert via SMS. In the end of this project, we will document all the hardware and software development and provide a simulation model of the system.